Inclusive and Localized Teaching and Learning Materials: An Action Research in a Sri Lankan Undergraduate ESL Classroom - Dharshini, K. (University of Jaffna, 2025)
Teaching materials are an integral part of education. The teaching materials that are used in classrooms should be more inclusive to all the learners in the classroom. No two learners are alike. A classroom may consist of diverse learners with wide variation in geography, climate, culture, language, and local customs. The textbooks and teaching materials have greater impact on the learners. Given the importance of recent developments in the relevance of localized teaching materials, the present Action Research study attempts to explore the need for inclusive teaching and localized teaching and learning materials in a multilingual and multicultural classroom context. Further, this study examines how traditional teaching resources on British and American English—affect students’ cultural identity and engagement. The study employs a qualitative action research approach with an intervention plan, which consists of four phases such as planning, action, observation, reflection suggested by Kemmis and McTaggart. The study was conducted with a group of 20 second year undergraduates in a lower level proficiency class in a Sri Lankan state university. The data were collected using classroom observations, student interviews, and content analysis of teaching materials and analyzed using thematic analysis. The findings indicate that the sole use of British and American English materials limit learners’ connection to their own cultural backgrounds, prior knowledge and potentially affect motivation and participation. Further, the findings after the intervention revealed that incorporating locally relevant materials have resulted in learners’ increased participation, motivation, engagement and to some extent the learners’ ensured their identity, voice and felt sense of valued in the classroom. Accordingly, the study provided useful insights into critically look at the material use in the ELT classroom and promotes the importance of incorporating localized materials.
Keywords: Inclusive; Localized materials; Cultural relevance; Participation; Engagement